Особенности профессиональной мотивации кинологов-спасателей государственной службы Украины по чрезвычайным ситуациям - Mordyushenko С. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
The article summarizes the results of rescue-dog handlers’ professional motivation research of State Emergency Service of Ukraine. Experimental data concerning the differences in the level of explication of the dominant motives at different stages of professionalism have been obtained. Rescue-dog handlers’ motivation profile has been constructed. Personal characteristics of rescue-dog handlers have been defined on the basis of directionality.